2021
DOI: 10.1021/acs.jpclett.0c03596
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Quantum-Well-Specific Carrier Mobilities in Layered Perovskites

Abstract: Layered organohalide perovskite films consist of quantum wells with concentration distributions tailored to enhance long-range charge transport. Whereas cascaded energy and charge funneling behaviors have been detected with conventional optical spectroscopies, it is not clear that such dynamics contribute to the efficiencies of photovoltaic cells. In this Letter, we use nonlinear photocurrent spectroscopy to selectively target charge transport processes within devices based on layered perovskite quantum wells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…Notably, the nonlinearity represented in Figure b is fundamentally different from a cascade of lower-order responses, such as those observed in off-resonant 2D Raman spectroscopies , because it provides dynamical information that is not available when a material absorbs a single laser pulse. For example, recent studies of layered perovskite systems demonstrate that recombination-induced nonlinearities can be exploited to resolve energy and charge funneling dynamics in layered perovskite systems on time scales of 100s of ps. , …”
Section: Signals Generation Mechanisms In Nonlinear Action Spectrosco...mentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, the nonlinearity represented in Figure b is fundamentally different from a cascade of lower-order responses, such as those observed in off-resonant 2D Raman spectroscopies , because it provides dynamical information that is not available when a material absorbs a single laser pulse. For example, recent studies of layered perovskite systems demonstrate that recombination-induced nonlinearities can be exploited to resolve energy and charge funneling dynamics in layered perovskite systems on time scales of 100s of ps. , …”
Section: Signals Generation Mechanisms In Nonlinear Action Spectrosco...mentioning
confidence: 99%
“…In our experience, NLPC decay profiles involving small quantum wells typically exhibit a sub-ns phase of nonradiative decay, which we refer to as T 1 , followed by a ∼10 ns phase of carrier drift, T 2 . To extract carrier transit times, the signals in Figure d are fit to sums of exponential functions: S ( τ ) = A 1 .25em exp ( τ / T 1 ) + A 2 .25em exp ( τ / T 2 ) The drift velocities are then computed using v drift = α –1 T 2 –1 , where α is the 7.48 μm –1 absorption coefficient of the film with 570 nm incident light (see the Supporting Information). With inspiration from conventional time-of-flight methods, , the potential is varied to extract a carrier mobility of μ = 0.083 ± 0.010 cm 3 /V/s from the data sets presented in Figure e. Here, the uncertainty of 0.010 cm 3 /V/s in the mobility is the standard error of the regression slope for the three points shown in Figure e. To account for the variability in fabrication conditions, these three velocities represent averages computed with four data sets acquired using three separate photovoltaic cells (see Supporting Information).…”
Section: Distinguishing Excitons and Free Charge Carriers With Tandem...mentioning
confidence: 99%
See 2 more Smart Citations
“…Second, we have developed nonlinear action spectroscopies to decompose the optical responses of photovoltaic cells into productive (photocurrent) and lossy (fluorescence) processes. Applications of these techniques are motivated by the inability of transient absorption experiments to distinguish energy and charge transfer mechanisms. Most recently, we have shown that trajectory-specific carrier mobilities can be determined for layered perovskite systems by cycling the laser pulse sequences and external biases applied to a photovoltaic cell . These experiments suggest promise in a new family of techniques that combine multidimensional spectroscopies with device measurements.…”
Section: Introductionmentioning
confidence: 98%